ANALYSIS OF FINANCIAL AND ECONOMIC FEASIBILITY OF CITY TRANSPORT CONVERSION TOWARDS BANDUNG TRANS METRO BUS - gugum Mukdas Sudarjah; Muhammad Ridwan; Erik Syawal Alghifari (Universitas Pasundan, 2021)
The low quality of transportation in Bandung City cannot be separated from poor planning. This can be seen when the Bandung City Government plans a solution to solving traffic jams by means of mass transportation or better known as Trans Metro Bandung. The purpose of transportation planning is to find solutions to transportation problems in the most appropriate way by using existing resources. This is in line with the costs involved in carrying out a process. The research focus is directed at how the government's efforts in implementing the policy of converting city transportation to bus rapid transit (BRT) are seen from a financial and economic standpoint. Research related to the financial and economic feasibility of public transportation in Indonesia has only been carried out a few times, this motivates researchers to conduct similar research to obtain findings about the phenomena that occur in an effort to improve public transportation services in Bandung City.